Keragaan Fenotipik Kedelai pada Dua Kondisi Intensitas Cahaya Ekstrim - RATNA ROHAENI, WAGE; TRIKOESOEMANINGTYAS,; WIRNAS, DESTA (Agrotrop : Journal on Agriculture Science; Vol 4 No 1 (2014), 2014)
Phenotypic of Soybean at Two Extreme Condition of Light Intensity. Cultivation of soybean inrow rubber area was one of extensification programme for improving national soybean production. Theproblem on row rubber area was the low light intensity that could disturb soybean growth. Plant breedingfor creating tolerant variety for low light intensity was doing until now. Bogor Agricultural University hadmany lines for being candidate of tolerant variety. F6 soybean population from single seed descentmethode need to explored for that trait on low light intensity condition. The aim of this research was toknow the differences of soybean phenotypic between on low light intensity and full light intensity condition.The research was done on March – May 2009. Randomized complete block design with 3 replicationwas using as experimental design which lines as the treatment on two condition (low light and full lightcondition). The result saw that low light intensity was changing type of soybean growth, determinatebecame indeterminate type of growth. Low light intensity made soybean became early on floweringfase and water content on seed was increase. Low light intensity made decreasing the productivity until37.25% than full light intensity condition.
Keywords: soybean; light intensity; phenotypic